RNA/DNA Ratio Performance of Blue Swimming Crab (Portunus pelagicus) Fed with Natural Food Phronima sp. and Artemia salina in Juvenile Phase - Sri Mulyani; Erni Indrawati; Syamsul Bahri (Jurnal Kelautan Tropis, 2023)
The availability and quality of fry is a major problem in blue swimming crab aquaculture, with the high mortality at the larval stage. RNA/DNA ratio is one of the parameters that can be used to evaluate the quality of crab fry, including health, nutrition, and growth conditions. This study aims to analyze the effect of Phronima sp. as a substitute feed for Artemia salina on the RNA/DNA ratio performance of blue swimming crab in juvenile phase (crablet 5) during rearing before cultivation in aquaculture ponds. This research was conducted at the Crab Hatchery Unit of the Brackish Water Aquaculture Fisheries Center (BPBAP) Takalar in February 2023. The study used a quantitative experimental completely randomized design (CRD) with five treatments and three repetitions. The ratio of Phronima sp. and Artemia sp. used were: Treatment A 100% Phronima sp; Treatment B 100% Artemia sp; Treatment C 75% Phronima sp and 25% Artemia sp; Treatment D 25% Phronima sp and 75% Artemia sp.;  and E: Phronima 75%+Artemia salina 25%. The results showed that Artemia salina combined with Phronima sp. increased the RNA/DNA ratio of the crab compared to a single feed (100% Phronima sp. or Artemia salina 100%). The feed combination with the highest RNA/DNA ratio was shown in treatment E (Phronima sp. 25% + Artemia salina 75%) with an RNA/DNA ratio of 2.02 +0.032 ng/µL.